Frequency of Anti-Toxoplasma IgM and IgG Antibodies in Leukemic Patients - M.J. Gharavi; M. Roozbehani; Z. Mandeh (Bihdād, 2015)
Aim: the efficacy and safety of combined therapy with anticholinergics and alpha blockers in comparison with alpha blockers monotherapy among patients with BPH.